Pemberdayaan Masyarakat Melalui Bank Sampah Induk Berseri Dikecamatan Lubuk Pakam Kabupaten Deli Serdang - Malem Syafitri; Evi Yunita Kurniaty (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2026)
Waste management remains a challenge in Lubuk Pakam District, Deli Serdang Regency, due to the increasing population and community activities. One effort to address this issue is through waste management-based community empowerment through the establishment of the Main Waste Bank Berseri (Serial Main Waste Bank). This study aims to determine the process of community empowerment through the Main Waste Bank Berseri and identify obstacles encountered in its implementation. This study uses a qualitative, descriptive approach. Data collection techniques included observation, interviews, and documentation, with informants including waste bank managers, government officials, and community members. The results of the study indicate that community empowerment through the Main Waste Bank Berseri has been running quite well, marked by increased community participation in waste management, economic benefits, and increased environmental awareness. However, there are still obstacles such as low participation of some communities and limited supporting facilities. Therefore, ongoing support and cooperation among the government, waste bank managers, and the community are needed for the program to run more effectively.